Hardware : efficient techniques for FAST corner detector - Lim, Teck Chuan (2017)
Corner detector is the foundation to many computer vision applications such as high-speed object recognition or object analysis. These applications are beginning to find their way in battery-operated devices such as smart-phones, drones, mobile robots, etc. The corner detection algorithm for these applications must therefore meet real time constraints while ensuring low power consumption. Software implementation on embedded platforms often fails to simultaneously meet these conflicting requirements. For example, low end embedded microcontrollers consume less power but are slow. On the other hand, high end processor consumes higher power to achieve high speed.